Seroepidemiology of SARS-CoV-2 on a partially vaccinated island in Brazil: Determinants of infection and vaccine response - Cerbino-Neto, José; Peres, Igor Tona; Varela, Margareth Catoia; Brandão, Luciana Gomes Pedro; Matos, Juliana Arruda de; Pinto, Luiz Felipe; Costa, Marcellus Dias da; Garcia, Márcio Henrique de Oliveira; Soranz, Daniel; Maia, Maria de Lourdes de Sousa; Krieger, Marco Aurélio; Cunha, Rivaldo Venâncio da; et al. (Frontiers in Public Health, 2022)
Background: A vaccination campaign targeted adults in response to the pandemic in the City of Rio de Janeiro. Objective: We aimed to evaluate the seroprevalence of SARS-CoV-2 antibodies and identify factors associated with seropositivity on vaccinated and unvaccinated residents. Methods: We performed a seroepidemiologic survey in all residents of Paquetá Island, a neighborhood of Rio de Janeiro city, during the COVID-19 vaccine roll-out. Serological tests were performed from June 16 to June 19, 2021, and adjusted seropositivity rates were estimated by age and epidemiological variables. Logistic regression models were used to estimate adjusted ORs for risk factors to SARS-CoV-2 seropositivity in non-vaccinated individuals, and potential determinants of the magnitude of antibody responses in the seropositive population. Results: We included in the study 3,016 residents of Paquetá (83.5% of the island population). The crude seroprevalence of COVID-19 antibodies in our sample was 53.6% [95%CI = 51.0, 56.3]. The risk factors for SARS-CoV-2 seropositivity in non-vaccinated individuals were history of confirmed previous COVID-19 infection [OR = 4.74; 95%CI = 3.3, 7.0], being a household contact of a case [OR = 1.93; 95%CI = 1.5, 2.6] and in-person learning [OR = 2.01; 95%CI = 1.4, 3.0]. Potential determinants of the magnitude of antibody responses among the seropositive were hybrid immunity, the type of vaccine received, and time since the last vaccine dose. Being vaccinated with Pfizer or AstraZeneca [Beta = 2.2; 95%CI = 1.8, 2.6] determined higher antibody titers than those observed with CoronaVac [Beta = 1.2; 95%CI = 0.9, 1.5]. Conclusions: Our study highlights the impact of vaccination on COVID-19 collective immunity even in a highly affected population, showing the difference in antibody titers achieved with different vaccines and how they wane with time, reinforcing how these factors should be considered when estimating effectiveness of a vaccination program at any given time. We also found that hybrid immunity was superior to both infection-induced and vaccine-induced immunity alone, and online learning protected students from COVID-19 exposure.